2013
DOI: 10.19173/irrodl.v14i1.1277
|View full text |Cite
|
Sign up to set email alerts
|

Learning in multiple communities from the perspective of knowledge capital

Abstract: In a learning system, multiple communities represent a networked structure of learning experiences. Individuals belong to multiple communities connected though complex relationships consisting of people, resources, rituals, and ties. Learning occurs as individuals traverse this network from one community to the next. This paper explores the question of how learning occurs in compound communities from the perspective of knowledge capital, that is, the communities' collective knowledge, skill, and perspective, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…learning in networks, learning in teams and learning in communities (see also, chapter 12, Vrieling-Teunter, Wopereis, Van den Beemt, De Laat, & Brand-Gruwel, this volume). In line with this work, Ozturk and Ozcinar (2013) observed that communities and sub communities exist in a networked structure. They wrote, "Learning in multiple communities requires a fuller understanding of the complexity of learning from diverse multiple communities which are connected in a social structure" (Ozturk & Ozcinar, 2013, p. 1).…”
Section: Community Buildingmultiple and Shifting Communitiessupporting
confidence: 84%
“…learning in networks, learning in teams and learning in communities (see also, chapter 12, Vrieling-Teunter, Wopereis, Van den Beemt, De Laat, & Brand-Gruwel, this volume). In line with this work, Ozturk and Ozcinar (2013) observed that communities and sub communities exist in a networked structure. They wrote, "Learning in multiple communities requires a fuller understanding of the complexity of learning from diverse multiple communities which are connected in a social structure" (Ozturk & Ozcinar, 2013, p. 1).…”
Section: Community Buildingmultiple and Shifting Communitiessupporting
confidence: 84%
“…SLCs provide students with a structured way to solve problems, share insight and help one another to develop new skills and expertise and advance dynamic collaborative learning (Fisher et al, 2021). A basic learning community includes people, resources, rituals, norms, dependency and ties, as well as nodes and holes within different communities (Ozturk and Ozcinar, 2013;Vesely et al, 2007), which could exist as a single community (Becket et al, 2012); or multiple/sub-set of communities in a network structure (Maddix, 2013). In the course evaluated for this study, students belong to two learning communities, the permanent team of 5-7 members and the entire class of 36 students.…”
Section: Literature Review Tlh Student Learning Communitiesmentioning
confidence: 99%
“…Other definitions place a similar emphasis on applying knowledge to practice, viewing communities as "individuals united in action" (Liedka, 1999, p. 5) or as groups with similar aims purposefully solving authentic problems within a real world context (Wick, 2000;Johnson, 2001). Since Wenger's original work on communities of practice in 1991 there has been a widespread increase in online learning, which has resulted in the adoption of the term "online communities of practice" to describe "socio-technological learning environments" that facilitate knowledge construction (Ozturk and Ozcinar, 2013).…”
Section: Communities Of Practicementioning
confidence: 99%